Sex Differences in Disgust: Why Are Women More Easily Disgusted Than Men?. (April 2018) - Al-Shawaf, Laith; Lewis, David M.G.; Buss, David M.
Women have consistently higher levels of disgust than men. This sex difference is substantial in magnitude, highly replicable, emerges with diverse assessment methods, and affects a wide array of outcomes—including job selection, mate choice, food aversions, and psychological disorders. Despite the importance of this far-reaching sex difference, sound theoretical explanations have lagged behind the empirical discoveries. In this article, we focus on the evolutionary-functional level of analysis, outlining hypotheses capable of explaining why women have higher levels of disgust than men. We present four hypotheses for sexual disgust and six for pathogen disgust, along with testable predictions. Discussion focuses on additional new hypotheses and on future research capable of adjudicating among these competing, but not mutually exclusive, hypotheses.